Penggunaan Metode Pembelajaran Bahasa Arab Didalam Kelas Yang Efektif - Asep Kurniawan; Adhe Nayla Shabrina; Allysa Sukma Santika; Edenia Silmy Kafi; Ahmad Fu’adin (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research was conducted to explore the use of effective classroom Arabic learning methods. Arabic is known as a language that is difficult to learn because of its complex language structure and the large number of vocabulary in Arabic. The method used in this research is qualitative, namely by distributing questionnaires to students of Hasmi Islamic High School which contains the use of Arabic learning methods. The purpose of this research is to find out the importance of using the right teaching method so that students can more easily learn and understand the teaching material delivered by the teacher. The results of this study indicate that a new policy is needed for the use of teaching methods in teaching and learning activities.